ANALYSIS OF LIGHTWEIGHT BRICK WASTE FOR PARTIAL SUBSTITUTION OF FINE AGGREGATE ON CONCRETE COMPRESSIVE STRENGTH - IHSAN TAQWA; YONAS PRIMA ARGA RUMBYARSO; LYDIA DARMIYANTI (CV KULTURA DIGITAL MEDIA, 2024)
The construction industry in Indonesia is experiencing a significant increase, fueled by government infrastructure development. Concrete is the material of choice as it is easy to use, economical and strong. However, excessive sand mining has a negative impact on the environment, including land degradation and pollution. The increase in construction has led to an increase in construction waste, which, if managed properly, can be profitable. Effective waste management is crucial to address environmental concerns and the utilization of waste lightweight bricks offers a cost-effective and efficient solution. Studies related to the use of waste lightweight bricks as a partial replacement for sand in concrete are highly relevant. The results of compressive strength testing on normal concrete at the age of 28 days obtained based on data analysis and discussion that has been presented in the previous chapter regarding the use of waste lightweight brick powder fibers with variations of 0%, 5%, and 10% are 439 kN (f´c 24.85 Mpa), while variation 1 of 10% lightweight brick powder waste reaches 344 kN (f´c 19.48 Mpa), and variation 2 of 15% lightweight brick powder waste reaches 308 kN (f´c 17.44 Mpa).